Structural and optical properties of ZnO thin film prepared by oxidation of Zn metal powders - Hassan, N.K; Hashim, M.R (Universiti Kebangsaan Malaysia, 2013)
High quality ZnO nanostructures have been fabricated at room temperature by a simple vacuum thermal evaporator from metallic Zn powders (99.999% purity) on a silicon (100) substrate. The Zn thin films were then transferred into a thermal tube furnace for oxidation at 700°C for different time durations. Time was found to be a critical factor in the synthesis. This was followed by characterization of their morphological, structural and optical properties. The morphology of the grown ZnO nanostructures exhibited several large grains, which increased gradually with increasing oxidation time. The crystallinity of the grown nanostructures was investigated using X-ray diffraction, revealing that the synthesized ZnO was in hexagonal wurtzite phase. The photoluminescence (PL) spectra of the fabricated ZnO nanostructures showed high intensity peak in the UV region due to near-band-edge (NBE) emission in which the structures oxidized for 30 min showing highest intensity.